2022
DOI: 10.1021/acsami.2c01587
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Cyclability and Rate Capability of SiOx via Dopamine Polymerization-Assisted Hybrid Graphene Coating for Advanced Lithium-Ion Batteries

Abstract: SiO x suffers from the 200% volume change during cycling and low electronic conductivity, resulting in poor cyclability and rate capability as a lithium-ion battery anode. Herein, we demonstrate a dopamine polymerization-guided carbon coating for SiO x anodes (SiO x @PDA@GNH). SiO x @PDA@GNH delivers charge capacities of 1269 and 1140 mA h·g–1 at charge rates of 0.05 and 3 C, respectively, and a capacity retention of 79.60% after 150 cycles at 1 C. A full cell with LiNi0.8Co0.1Mn0.1O2 or cathode demonstrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Gu et al 78 demonstrated a simple way to coat SiO x with polydopamine (PDA) with rich hydroxyl groups; PDA is able to form a stable carbon layer on the surface of SiO x (SiO x @PDA@GNH). The functional groups on dopamine can bond with the graphene nanotube hybrid (GNH) to form a hybrid layer, and the coating layer is evenly distributed and has good electrolyte wetting properties.…”
Section: Structural Design Of Siox/c Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu et al 78 demonstrated a simple way to coat SiO x with polydopamine (PDA) with rich hydroxyl groups; PDA is able to form a stable carbon layer on the surface of SiO x (SiO x @PDA@GNH). The functional groups on dopamine can bond with the graphene nanotube hybrid (GNH) to form a hybrid layer, and the coating layer is evenly distributed and has good electrolyte wetting properties.…”
Section: Structural Design Of Siox/c Compositesmentioning
confidence: 99%
“…Overgrowth and suppressed cracking of the SEI layer are considered crucial factors that significantly impact performance, and the tight coating of SiO x with the carbon layer avoids contact between SiO x and the electrolyte, thus forming a stable SEI film to enhance the cycle performance. Gu et al 78 demonstrated a simple way to coat SiO x with polydopamine (PDA) with rich hydroxyl groups; PDA is able to form a stable carbon layer on the surface of SiO x (SiO x @P-DA@GNH). The functional groups on dopamine can bond with the graphene nanotube hybrid (GNH) to form a hybrid layer, and the coating layer is evenly distributed and has good electrolyte wetting properties.…”
Section: Core-shell Sio X /Cmentioning
confidence: 99%
“…This composite anode demonstrated a specific capacity of about 1120 and 417 mAh g −1 after 500 cycles at 1.0 and 16.5 A g −1 , respectively. PDA coating on SiO x developed by Gu et al [112] showed better wetting properties with water and electrolyte solution. It delivered an initial Columbic efficiency of 80.48% and excellent specific capacities of about 1270 and 1140 mAh g −1 at 0.05 and 3 C, respectively, and a capacity retention of about 80% after 150 cycles at 1 C.…”
Section: Silicon-based Anodesmentioning
confidence: 99%
“…13,14 However, pure SiO x materials also suffer from some drawbacks, such as low conductivity and inevitable volume expansion (≈200%). 15 Many strategies have been proposed to solve the above mentioned problems, such as SiO x /C composites, [16][17][18] constructing SiO x nanostructures, 19 and the optimization of conductive agents and binders. 20,21 However, SiO x can hardly be applied on a large scale because of the lack of mature raw materials and desirable structural design with both good mechanical strength and ion/electron transport pathways.…”
Section: Introductionmentioning
confidence: 99%